Structural properties and anti-inflammatory activity of purified polysaccharides from Hen-of-the-woods mushrooms (Grifola frondosa) - Liu, Xiaoyi; Chen, Shuai; Liu, Huijuan; Xie, Jiao; Hasan, K. M. Faridul; Zeng, Qibing; Wei, Shaofeng; Luo, Peng (Frontiers in Nutrition, 2023)
Grifola frondosa is an edible medicinal mushroom that has been proven to have a variety of health benefits. The main active ingredients of this mushroom are polysaccharides. In this study, ultrasonic-assisted extraction was used to obtain crude Grifola frondosa polysaccharides (GFPs). Then, purified GFP was obtained after purification. The optimum extraction conditions were an extraction time of 71 min, an extraction temperature of 90°C in a solid-to-liquid ratio of 1:37 g/mL, and an ultrasonic power of 500 W. GFP was purified using DEAE-52 and Sephadex G-100. The structural characterization of GFP was performed using Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), ion chromatography (IC), and ultraviolet (UV) visible photometry. The morphology of GFP was analyzed by scanning electron microscopy (SEM), thermogravimetric differential scanning calorimetry (TG-DSC), and Congo red testing. In addition, the administration of GFP in oxazolone (OXZ)-induced ulcerative colitis (UC) in mice was found to prevent weight loss. Different doses of GFP (80, 160, and 320 mg/kg body weight) were used, and sulfapyridine (SASP) was used as a positive control (370 mg/kg body weight) for the treatment of OXZ-induced UC. After treatment, the mice were killed, and blood and colon tissue samples were collected. GFP was found to prevent decreases in colon length and the levels of leukocytes, platelets, and neutrophils in UC mice. Moreover, GFP also decreased the expression of pro-inflammatory cytokines [tumor necrosis factor (TNF)-α and interleukin (IL)-1 β], increased IL-10, and reduced colon injury in UC mice. The results showed that Under these conditions, the predicted polysaccharide yield was 21.72%, and the actual extraction rate was 21.13%. The polysaccharide composition (molar ratio) was composed of fucose (0.025), glucosamine hydrochloride (0.004), galactose (0.063), glucose (0.869), and mannose (0.038). GFP was also found to have a typical absorption peak, and the GFP extracted using the ultrasound-assisted extraction protocol was mainly β-glucan. These results indicate that ultrasound-assisted extraction of GFP could reduce OXZ-induced intestinal inflammation as a promising candidate for the treatment of UC, with the potential for development as a food supplement to improve intestinal diseases.